2003
DOI: 10.1207/s1532785xmep0504_02
|View full text |Cite
|
Sign up to set email alerts
|

Viewer Aggression and Attraction to Television Talk Shows

Abstract: Guided by the uses and gratifications perspective, we examined how dispositional factors-aggression, anger, attitudes toward women, and communication anxiety and reward-and television-viewing factors-motivation, attitudes, topics, emotions, and parasocial interaction-explained attraction to different TV talk shows.We considered how these dispositional and viewing factors discriminated among different talk show preferences and different levels of aggression. Compared with The Oprah Winfrey Show viewers, Jerry S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 78 publications
(69 reference statements)
1
11
0
1
Order By: Relevance
“…All the correlations (except for time spent with the medium) were found to be significant for both follower sets. This is consistent with decades of PSI research that found that affinity (Rubin, 1979(Rubin, , 1981, instrumental media use (Kim & Rubin, 1997;Rubin et al, 1985), perceived realism (Rubin & Perse, 1987;Rubin et al, 2003;Rubin et al, 1985), uncertainty reduction (Perse & Rubin, 1989), social attraction (Rubin & McHugh, 1987), and attitude homophily (Turner, 1993) correlated with PSI. Though most PSI correlations were significant, three were found to be of moderate strength for followers of the social athlete (i.e., uncertainty reduction, attitude homophily, and instrumental media use) and four were found to be of moderate strength for the followers of the parasocial athlete (i.e., uncertainty reduction, attitude homophily, instrumental media use, and perceived realism).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…All the correlations (except for time spent with the medium) were found to be significant for both follower sets. This is consistent with decades of PSI research that found that affinity (Rubin, 1979(Rubin, , 1981, instrumental media use (Kim & Rubin, 1997;Rubin et al, 1985), perceived realism (Rubin & Perse, 1987;Rubin et al, 2003;Rubin et al, 1985), uncertainty reduction (Perse & Rubin, 1989), social attraction (Rubin & McHugh, 1987), and attitude homophily (Turner, 1993) correlated with PSI. Though most PSI correlations were significant, three were found to be of moderate strength for followers of the social athlete (i.e., uncertainty reduction, attitude homophily, and instrumental media use) and four were found to be of moderate strength for the followers of the parasocial athlete (i.e., uncertainty reduction, attitude homophily, instrumental media use, and perceived realism).…”
Section: Discussionsupporting
confidence: 86%
“…PSI research over the last 3 decades has examined the relationships between audience members and newscasters (Palmgreen, Wenner, & Rayburn, 1980;Rubin et al, 1985), television performers (Rubin & McHugh, 1987), soap opera characters (Perse & Rubin, 1989;Rubin & Perse, 1987, Sood & Rogers, 2000, and television and radio talk-show hosts (Rubin, Haridakis, & Eyal, 2003;Rubin & Step, 2000). PSI research has also been conducted on television shopping hosts (Grant, Guthrie, & Ball-Rokeach, 1991;Gudelunas, 2006), reality-based television programming (Nabi, Stitt, Halford, & Finnerty, 2006), and print-media sources such as romance novels (Burnett & Beto, 2000).…”
Section: Review Of Literature Psimentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on verbal violence as one of the most common types of content used to attract television viewers' attention. Verbal violence, broadly defined as "noxious symbolic messages containing criticism, insults, cursing, or a negative affective reaction" (Greenberg, 1980, p. 108), is a common form of sensational content that is particularly widespread in talk shows (Wood, 4 2001, Rubin et al, 2003, where the setting is often intentionally organized in order to spectacularize verbal confrontations (Hutchby, 2001;Luginbühl, 2007). In recent years, the portrayal of verbal violence in television programs has increased substantially, while that of physical violence has remained relatively unchanged Vaughan, 1997, Gunter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%